Exploring T.S. Eliot’s The Waste Land as a Pre-postmodern Text - Rajbhandari, Jitendra Man (Journal of Development Review, 2023)
Despite being a groundbreaking literary work of Modernism, T.S. Eliot’s poem The Waste Land heralds the new era of Postmodernism that officially begins almost two decades after its publication. Although Eliot is one of the best representatives of modernist poets, his major work The Waste Land foreshadows some postmodern techniques and concepts. A seminal modernist poem of 1922, it can also be read as a postmodernist poem in the making. The present paper analyses some postmodern elements in The Waste Land and finds it a great epic of pre postmodernist thoughts. Its intertextuality, fragmentation, discontinuity in narrative structure, and deconstruction of meaning put The Waste Land closer to postmodernism.